Long-term exposure to ambient PM2.5 associated with fall-related injury in six low- and middle-income countries. (June 2018) - Guo, Yanfei; Lin, Hualiang; Shi, Yan; Zheng, Yang; Li, Xing; Xiao, Jianpeng; Liu, Tao; Zeng, Weilin; Vaughn, Michael G.; Cummings-Vaughn, Lenise A.; Nelson, Erik J.; Qian, Zhengmin (Min); et al.
Abstract: Exposure to ambient air pollution has been linked with adverse health outcomes of the circulatory and nervous systems. Given that falls are closely related to circulatory and nervous health, we hypothesize that air pollution may adversely affect fall-related injury. We employed Wave 1 data from 36, 662 participants aged ≥50 years in WHO's Study on Global AGEing and Adult Health in six low- and middle-income countries. Ambient annual concentration of PM2.5 was estimated using satellite data. A three-level logistic regression model was applied to examine the long-term association between ambient PM2.5 and the prevalence of fall-related injury, and associated disease burden, as well as the potential effect modification of consumption of fruit and vegetables. Ambient PM2.5 was found to be significantly associated with the risk of fall-related injury. Each 10 μg/m 3 increase corresponded to 18% (OR = 1.18, 95% CI: 1.09, 1.28) increase in fall-related injury after adjusting for various covariates. The association was relatively stronger among participants with lower consumption of fruit (OR = 1.22, 95% CI: 1.12, 1.33) than higher consumption (OR = 1.06, 95% CI: 0.92, 1.23), and among those with lower vegetable consumption (OR = 1.18, 95% CI: 1.08, 1.28) than higher consumption (OR = 1.08, 95% CI: 0.91, 1.27). Our study suggests that ambient PM2.5 may be one risk factor for fall-related injury and that higher consumption of fruit and vegetables could alleviate this effect. Graphical abstract: Image 1 Highlights: Each 10 μg/m 3 increase corresponded to 18% increase in fall-related injury. Higher consumption of fruit and vegetables might mitigate the adverse effects of ambient PM2.5 . Ambient PM2.5 may be one risk factor for fall-related injury.